2010
DOI: 10.1080/09537280903317049
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing performance: an analysis of the structure and functions of performance management reviews

Abstract: This article proposes an analytical framework for conceptualising performance management reviews (PMRs). Drawing on multiple literatures, the article applies Pettigrew et al.'s (Pettigrew, A., Whipp R., and Rosenfield R., 1989. Competitiveness and the management of strategic change processes. In: A. Francis, and P.K.M. Tharakan, eds. The competitiveness of European industry: country policies and company strategies. London: Routledge) framework to develop our understanding of the context, process and content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 57 publications
0
18
0
6
Order By: Relevance
“…When used interactively, the BSC also functioned as a framework for organizing verbal and mental thought processes for examining the relevance of basic assumptions of the company's objectives, strategy and operations. Moreover, echoing earlier research (Martinez et al, 2010), PM meetings seemed to be the central element that linked performance information and action and enabled the BSC to be closely tied to the belief and boundary systems, thus making it a fundamental tool that employees would extensively use.…”
Section: Discussionmentioning
confidence: 71%
“…When used interactively, the BSC also functioned as a framework for organizing verbal and mental thought processes for examining the relevance of basic assumptions of the company's objectives, strategy and operations. Moreover, echoing earlier research (Martinez et al, 2010), PM meetings seemed to be the central element that linked performance information and action and enabled the BSC to be closely tied to the belief and boundary systems, thus making it a fundamental tool that employees would extensively use.…”
Section: Discussionmentioning
confidence: 71%
“…The differences in the use of WA are examined in three dimensions: the selection of WA metrics, the processing of WA data, and the organizational context of WA use (adapted from Pettigrew, Whipp, & Rosenfield, 1989). A similar approach has been used in the performance measurement literature (Bourne et al, 1999;Bourne, Neely, Platts, & Mills, 2002;Bourne, Kennerley, & Franco-Santos, 2005;Martinez, Pavlov, & Bourne, 2010). However, this study extends Pettigrew et al's (1989) model by demonstrating how it can be applied in marketing performance measurement research.…”
Section: Introductionmentioning
confidence: 58%
“…Pettigrew et al's (1989) framework was selected as a guide for this study because it provides a sound structure for organizing disparate findings from the performance measurement literature to develop a holistic understanding of the elements that affect the firm's ability to design and exploit a marketing metrics system. The framework has been adopted in a number of studies on the use of performance measurement systems, all of which have concluded that the content, process, and context of performance measurement affect the outcome of the system (Bourne et al, 1999;2002;2005;Martinez et al, 2010). In these studies, the dimensions have been adapted to better harmonize with performance measurement research and the precise research questions.…”
Section: Framework For Investigating the Use Of Performance Metrics Smentioning
confidence: 99%
See 1 more Smart Citation
“…PMS and any other control could be used diagnostically or interactively (Simons 1995, Tessier andOtley 2012). The 'diagnostic' role of control focuses on controlling the 'critical performance variables' or those key factors a firm should pay attention to in order to succeed in implementing its deliberate strategy (Dixon, Nanni, and Vollmann 1990;Martinez, Pavlov, and Bourne 2010;Micheli and Manzoni 2010;Tessier and Otley 2012). In this context, since managers are frequently not in a condition to justify with data the assumptions underlying their organization's competitive strategy (Buytendijk, Hatch, and Micheli 2010;Silvestro 2016), BPA should enable identifying the causal effects between impact factors -expressed in qualitative/non-financial terms -and strategic target measures.…”
Section: From Business Analytics To Business Performance Analyticsmentioning
confidence: 99%